THE INCORPORATION OF ARTIFICIAL INTELLIGENCE IN CONTEMPORARY INDONESIAN PHOTOGRAPHY (A VISUAL REPRESENTATION STUDY OF SONGKET PANDAI SIKEK) - Muhammad Iqbal; Roza Muliati (PT. Antis International Publisher, 2026)
Objective: The issue addressed in this study arises from the increasing use of artificial intelligence in contemporary photography, which has the potential to alter the way cultural artifacts are represented. Songket Pandai Sikek, as a visual object rich in historical and symbolic meaning, undergoes aesthetic transformation when processed using AI technology. This raises questions about the extent to which such digital representations can maintain cultural identity or whether they shift the artifact into a purely aesthetic object. This research aims to explore the integration of artificial intelligence in contemporary photography through a case study of the visual representation of Songket Pandai Sikek, while examining the visual changes that occur in the process. Method: The study employs a qualitative approach through visual analysis and case study methods. Comparisons are made between traditional photographs of songket and images generated using AI to identify changes in patterns, textures, colors, and emerging aesthetic characteristics. Results: The findings indicate that AI technology can enhance songket details, sharpen colors, and produce more symmetrical compositions. These transformations expand the possibilities for photographers' visual expression but tend to shift the songket into a mere aesthetic object, potentially diminishing the cultural values that should remain present. Novelty: The integration of AI holds significant potential for innovation in culture-based photography, but it also carries the risk of meaning distortion if not accompanied by sufficient cultural understanding. As a recommendation, strong cultural literacy and ethical guidelines are needed for photographers, digital artists, and researchers to ensure that the use of AI in visual representation continues to respect the symbolic values, cultural identity, and historical context of Songket Pandai Sikek.